Karakteristik Serat Kasar dan Kapasitas Antioksidan Biskuit dengan Substitusi Tepung Biji Alpukat (Persea Americana) terhadap Tepung Terigu - Kadek Dyah Swasni Prambandita; Nyoman Wahyu Meta Wulandari (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
One of the by-products that can be used as a source of fiber and antioxidants is avocado seeds. Processing avocado seeds into flour can make it easier for people to make interstitial foods, for example biscuits. Avocado seed biscuits that are rich in fiber and antioxidants are expected to be beneficial for health. This study aims to determine the effect of the right ratio of wheat and avocado seed flour on the chemical characteristics of biscuits, The study used a complete random design with the treatment of the comparison of wheat and avocado seed flour, namely F1 (100:0), F2 (90:10), F3 (80:20), F4 (70:30), F5 (60:40), F6 (50:50). The determination of the best biscuits is seen based on the parameters observed, namely: moisture content test, crude fiber test, antioxidant capacity, IC50 value. Based on the results of the analysis of various comparisons of wheat and avocado seed flour (TBA) in biscuits, it showed no real effect (p>0.05) on water content, while there was a real effect (p>0.05) on crude fiber, IC50, and antioxidant capacity.